Estudio de voltaje de paso y voltaje de toque mediante la implementación de un módulo didáctico. - Broncano Taipe, Elvis Paúl (2020)
The present technological proposal was framed in the ignorance of the variation of step and touch voltage in front of the change of the resistivity in the different types of soil, where the grounding is installed, which in many cases could cause accidents and incidents in electrical operations. This is why this research project was based on in the evaluation of the step and touch voltage, through a grounding grid programmed in a virtual prototype, which allowed to determine the tolerable limits of the energy that passes through the human body based on the different positions that it takes inside an electrical installation. Bibliographic and field methodology was used to collect the information through a hypothetical inductive method, which was counteracted by the construction of a prototype programmed in a three-dimensional mesh in the HTML program, which facilitated the visualization of the position of the person, in addition to demonstrating the variations of the step and touch potential, which occur at the time of a failure either internal or external, in this way it was possible to evaluate the voltage and energy in each one of the simulations of the circuits, in various positions and with different resistivity of the ground. It was obtained as a result that, in the step and touch voltage, while the resistance of the ground increases, the energy which through the human body is high, while, if it decreases, the energy is low.